Teaching poetry at primary and secondary school level : an examination of students' and teachers' attitudes to poetry - Forde, Marian (Trinity College (Dublin, Ireland). School of Education, 2011)
Over the past twenty years of teaching poetry at second level and working with second level student teachers and recently qualified primary school teachers in Trinity College, it has become apparent that poetry is the least liked and most poorly taught part of the English curriculum. Historically poetry was an integral part of all students’ education, it was valued for its moralistic and disciplinary function. Anecdotal evidence suggests that it was used for the betterment of society. The present situation of poetry is very different, it has been pushed aside in some schools, it is often badly taught and teachers themselves say they are ill equipped to teach it. The aims of this study are to elucidate the historical and educative role of poetry, to establish a comprehensive and reliable baseline of students’ and teachers’ attitudes to the study of poetry in classrooms and of their perceived understanding of its value in people’s lives in contemporary society, and finally, to evaluate the impact of a specially devised creative and interactive approach to the teaching of poetry with recently qualified primary school teachers.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin